IDENTIFIKASI RISIKO PADA OKRA MENGGUNAKAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) DI PT. MITRATANI DUA TUJUH DI KABUPATEN JEMBER - Ida Bagus Suryaningrat; Wiwik Febriyanti; Winda Amilia (Faculty of Agricultural Technology, University of Jember, 2019)
Post-harvest is an activity processed from harvesting to becoming a product. Post-harvest handling aims to maintain the quality and minimize the loss of the agricultural product. Post-harvest loss of okra is the reduction of the okra harvest amount from picking up to transporting process. Many factors can cause the post-harvest loss of okra. This study aimed to determine the causal sources of the okra loss. This study used FMEA and fishbone diagram. Fishbone diagram was used to identify the causes of the okra loss in a fishbone skeleton. FMEA was used to give the value on the causes of the okra loss by assessing the severity, occurrence and detection to get the RPN value. The RPN value was used to rank the potential causes of the loss. From the result of the study, it was found that there were 4 main factors causing the okra loss which had the RPN value above the RPN critical value. It were lack of picker accuracy and training or counseling, handling pets and diseases, and age factor of picker. Keywords: fishbone diagram, FMEA, okra, post-harvest loss